Dengue during pregnancy and adverse fetal outcomes: a systematic review and meta-analysis. Issue 7 (July 2016) - Paixão, Enny S; Teixeira, Maria Gloria; Costa, Maria da Conceição N; Rodrigues, Laura C
Summary: Background: Little is known about the possible adverse effects of dengue infection during pregnancy on fetal outcomes. In this systematic review and meta-analysis we aimed to estimate the increase in risk of four adverse fetal outcomes in women who had dengue infection during pregnancy. Methods: For this systematic review and meta-analysis, we searched Medline, Embase, Global Health Library, and Scopus for articles published before Aug 1, 2015. We included original studies that reported any fetal outcomes for pregnant women who had dengue infection during the gestational period. Case-control, cohort, and cross-sectional studies and unselected case series were eligible for inclusion. We excluded case reports, ecological studies, reviews, in-vitro studies, and studies without data for pregnancy outcomes. We independently screened titles and abstracts to select papers for inclusion and scored the quality of those included in meta-analyses. For each study, we recorded study design, year of publication, study location, period of study, and authors and we extracted data for population characteristics such as the number of pregnancies, dengue diagnostic information, and the frequency of outcomes. We investigated four adverse fetal outcomes: stillbirth, miscarriage, preterm birth, and low birthweight. We estimated the increase in risk of these adverse fetal outcomes by use of Mantel-Haenszel methods. We assessed heterogeneity of odds ratios (OR) with the I 2 statistic. Findings: We identified 278 non-duplicate records, of which 107 full-text articles were screened for eligibility. 16 studies were eligible for inclusion in the systematic review and eight were eligible for the meta-analyses, which included 6071 pregnant women, 292 of whom were exposed to dengue during pregnancy. For miscarriage, the OR was 3·51 (95% CI 1·15–10·77, I 2 =0·0%, p=0·765) for women with dengue infection during pregnancy compared with those without. We did not do a meta-analysis for stillbirth because this outcome was investigated in only one study with a comparison group; we calculated the crude relative risk to be 6·7 (95% CI 2·1–21·3) in women with symptomatic dengue compared with women without dengue. Preterm birth and low birthweight were the most common adverse pregnancy outcomes. The OR for the association with dengue was 1·71 (95% CI 1·06–2·76, I 2 =56·1%, p=0·058) for preterm birth and 1·41 (95% CI 0·90–2·21, I 2 =0·0%, p=0·543) for low birthweight. Interpretation: Evidence suggests that symptomatic dengue during pregnancy might be associated with fetal adverse outcomes. If confirmed, it would be important to monitor pregnancies during which dengue is diagnosed and to consider pregnant women in dengue control policies. Funding: National Council for Scientific and Technological Development (CNPq).